Trialling environmental sensors in Tanzanian schools – first pilot - Toyinbo, Oluyemi; Villavicencio, Xuzel; Haßler, Björn (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257287 ZenodoArchiveConcept: 10257286 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1035 2129771:NFNWZX3A
Keywords: _comingsoon; _r:AddedByMyEducationEvidence